High-throughput structural characterisation of therapeutic protein targets. - Marsden, B; Sundstrom, M; Knapp, S (2006)
The overarching scientific objective for high-throughput structural biology projects targeting human proteins or relevant proteins of human pathogens is to generate a detailed structural insight of biologically relevant structural features of soluble or membrane protein families of therapeutic relevance. These data will better enable structure-guided drug discovery in pharmaceutical and biotechechnology companies. In particular, detailed structural descriptions for entire protein families will be highly valuable for the design of drugs and other bioactive compounds that are selective for individual members or groups of proteins within protein families. In addition to determined structural information, targeted high-throughput structural biology will also provide reagents, methodologies, technologies and small molecules that bind selectively to targets that are suitable as intervention points in the treatment of disease.